2015
DOI: 10.4314/ajtcam.v12i5.5
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis of <i>Cyrtanthus obliquus</i> bulbs from the informal street market of Kwazulu-Natal, South Africa

Abstract: Background: Cyrtanthus obliquus is a medicinal plant commonly known by the locals in South Africa as Umathunga. It is used in traditional South African medicine for the treatment of scrofula, chronic coughs and headaches and is also used to prepare the popular decoction known as Imbiza. Materials and methods: The secondary metabolites from C. obliquus bulbs were extracted using solvent extraction techniques, isolated using column chromatography and identified using spectroscopic techniques. The antioxidant pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In this regard, four homoisoflavanones (40)(41)(42)(43) were described from a CH 3 OH extract of the 'Knysna lily' Cyrtanthus obliquus (L.f.) Aiton [70]. Measurements made via the FRAP assay showed all four compounds to have antioxidant potential [70]. Further analysis with the DPPH free radical scavenging reagent revealed that the 3-benzylidenechromanones (40,41) were inactive, while the 3-benzylchromanones (42,43) This article is protected by copyright.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, four homoisoflavanones (40)(41)(42)(43) were described from a CH 3 OH extract of the 'Knysna lily' Cyrtanthus obliquus (L.f.) Aiton [70]. Measurements made via the FRAP assay showed all four compounds to have antioxidant potential [70]. Further analysis with the DPPH free radical scavenging reagent revealed that the 3-benzylidenechromanones (40,41) were inactive, while the 3-benzylchromanones (42,43) This article is protected by copyright.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…By contrast, galanthamine (5) administered peritoneally at 2 mg/kg/day was seen to reverse all of the deleterious effects brought about by the carcinogen DMH [69]. There has also been interest in the contributions of non-alkaloid principles towards the antioxidant effects of the Amaryllidaceae [70]. In this regard, four homoisoflavanones (40)(41)(42)(43) were described from a CH 3 OH extract of the 'Knysna lily' Cyrtanthus obliquus (L.f.) Aiton [70].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Species of Cyrtanthus have been identified as reservoirs for a host of chemical compounds. In a study performed by Mahlangeni et al, four homoisoflavanones, namely 5,7-dihydroxy-6-methoxy-3-(4′-methoxybenzyl)chroman-4-one, 5,7-dihydroxy-6-methoxy-3-(4′hydroxybenzyl)chroman-4-one and two 5,7-dihydroxy-6-methoxy-3-(4′-methoxybenzylidene)chroman-4-one, 5,7-dihydroxy-3-(4′hydroxybenzylidene)-chroman-4-one were isolated from the hexane, methanol and dichloromethane extracts of Cyrtanthus obliquus [ 338 ]. The bulbs of C. obliquus extracted with ethanol also revealed the presence of novel alkaloid obliquine, as well as 1α-hydroxygalanthamine, 3-epimacronine, narcissidine, tazettine and trisphaeridine [ 339 ].…”
Section: The Genus Cyrtanthusmentioning
confidence: 99%
“…dihydroxy-6-methoxy-3-(4′-methoxybenzyl)chroman-4-one and 5,7-dihydroxy-6-methoxy-3-(4′-hydroxybenzyl)chroman-4-one isolated from the fresh bulbs of C. obliquus have been shown to possess significant antioxidant activity with an IC50 of 371.54 and 288.40 µg/mL, respectively[338].…”
mentioning
confidence: 99%